Intermittent Fasting to the Eye: A New Dimension Involved in Physiological and Pathological Changes - Feng, Jiaqing; Zhang, Shijiao; Li, Wenning; Bai, Tianle; Liu, Yulin; Chang, Xingyu (Frontiers in Medicine, 2022)
Intermittent fasting (IF) can cause changes in the body's energy metabolism, which can alter the body's state and affect the course of many diseases. Recent studies have shown that intermittent fasting can change the local metabolism of the eye, inhibit the inflammatory response, and have a therapeutic effect on ocular diseases. In addition, intermittent fasting can also change the composition of the gut microbiome, which can impact systemic and visual parameters. This article reviews the progress of research on the correlation between intermittent fasting and biological parameters and pathological changes in the eye, to provide some reference for ocular treatment.